PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN 024 SALUPAKU - Farida; Afni, Nur; Supriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading skill is a foundational literacy capability in primary education. However, many first-grade students still experience difficulties in mastering basic reading due to unstimulating visual media during instruction. This study aims to analyze the improvement of early reading skills among first-grade students at SDN 024 Salupaku through the implementation of picture media (Big Book). A Classroom Action Research (CAR) design following the Kemmis and McTaggart model was conducted with 25 first-grade students (10 males and 15 females) as research subjects. Data were collected using performance tests, systematic observations, and audio-visual recordings, then analyzed through descriptive qualitative and quantitative techniques. The findings revealed a significant enhancement in student reading performance across cycles. In Cycle I, the average class score reached 73.4 with a classical completeness rate of 64% (moderate category), which failed to meet the target minimum indicator of 75%. Following refined interventions in Cycle II, the average class score increased to 89.72 with a 100% classical completeness rate (very high category). The evaluation across four key parameters pronunciation, intonation, fluency, and voice clarity demonstrated substantial progress. It is concluded that the implementation of picture media effectively enhances the early reading skills of first-grade elementary students